On Soft \(Ig^*\) Closed Sets in Soft Ideal Topological Spaces - Inthumathi, V.; Chitra, V.; Ponmani, K. (Journal of Informatics and Mathematical Sciences, 2017)
In this paper we introduce and study the notions of soft \(Ig^{*}\) closed sets in soft ideal topological spaces and investigate some of their properties.